Respuesta :

9514 1404 393

Answer:

  14. (x, y) = (1, 3)

  15. $6200

Step-by-step explanation:

14. Substitution is a nice strategy for this one, since we have an expression for y. Using the second equation in the first, we get ...

  4x +(2x+1) = 7

  6x +1 = 7 . . . . . . . collect terms

  6x = 6 . . . . . . . subtract 1

  x = 1 . . . . . . . divide by 6

  y = 2(1) +1 = 3 . . . . substitute for x in the second equation

The solution is (x, y) = (1, 3).

__

15. The formula for the balance when the investment earns simple interest is ...

  A = P(1 +rt)

where P is the principal invested, r is the annual rate, and t is the number of years.

For the given values, we find the account balance to be ...

  A = $5000(1 +0.04·6) = $5000·1.24 = $6200

Jacob will have $6200 in his account after 6 years.